Impact of COVID-19 vaccination on tinnitus onset and severity: a comprehensive survey study - Yellamsetty, Anusha; Etu, Egbe-Etu; Bao, Shaowen (Frontiers in Audiology and Otology, 2025)
PurposeThe primary objective of this study was to investigate the prevalence and characteristics of tinnitus related to COVID-19 vaccination. Specifically, we aimed to assess the impact of COVID-19 vaccination on the onset and severity of tinnitus, including changes in loudness, pitch, anxiety, and speech perception. Additionally, we sought to identify potential risk factors associated with new-onset tinnitus and the exacerbation of pre-existing symptoms.DesignA comprehensive survey was administered to 372 individuals who reported new-onset tinnitus or worsening of pre-existing tinnitus following COVID-19 vaccination. Data on tinnitus characteristics before and after COVID-19 vaccination were collected. The survey documented pre-existing medical conditions, and changes in tinnitus loudness, pitch, and related anxiety. Respondents were divided into two groups: those with pre-existing tinnitus and those with new-onset tinnitus following vaccination. Statistical analyses were conducted to compare changes across these groups and to explore associations with vaccine type (mRNA vs. non-mRNA) and pre-existing medical conditions.ResultsOf the respondents, 53% with pre-existing tinnitus reported worsened symptoms following vaccination, with significant increases in loudness, pitch, and anxiety. Additionally, 47% of respondents developed new-onset tinnitus, with this group reporting higher severity and anxiety levels compared to those with pre-existing tinnitus. There was no significant difference in tinnitus onset latency between mRNA vaccines (Pfizer and Moderna) and non-mRNA vaccines (Johnson & Johnson). Pandemic-related anxiety was identified as a contributing factor to the exacerbation of tinnitus symptoms.ConclusionsThe results indicate that COVID-19 vaccination is associated with an increased risk of both new-onset tinnitus and worsening pre-existing tinnitus. Significant increases in tinnitus loudness, pitch, and anxiety post-vaccination, along with challenges in speech perception, emphasize the need for further research into the auditory effects of COVID-19 vaccination. Identifying risk factors, such as underlying health conditions and psychological stress, will be crucial in developing strategies for the management and treatment of tinnitus in vaccinated individuals.